2020
DOI: 10.1038/s41598-020-64094-1
|View full text |Cite
|
Sign up to set email alerts
|

The greenhouse gas offset potential from seagrass restoration

Abstract: Awarding CO2 offset credits may incentivize seagrass restoration projects and help reverse greenhouse gas (GHG) emissions from global seagrass loss. However, no study has quantified net GHG removal from the atmosphere from a seagrass restoration project, which would require coupled Corg stock and GHG flux enhancement measurements, or determined whether the creditable offset benefit can finance the restoration. We measured all of the necessary GHG accounting parameters in the 7-km2Zostera marina (eelgrass) mead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 73 publications
1
44
4
Order By: Relevance
“…Regardless of the exact mechanism, the net gain of sediment C at the outer sites shows that the meadow-wide MHW did not cause meadow-wide C losses. A related study mapping blue C in this meadow showed an increase in meadow-wide sediment C stocks from 2013 to 2016, despite the localized loss of sediment C in the inner meadow (Oreska et al, 2020). Our study confirms these findings and shows that disturbance from a MHW can have non-uniform effects on seagrass loss and recovery and on sediment C stock persistence at the meadow-scale (km 2 ).…”
Section: Spatial and Temporal Patterns In Blue C Losssupporting
confidence: 85%
See 2 more Smart Citations
“…Regardless of the exact mechanism, the net gain of sediment C at the outer sites shows that the meadow-wide MHW did not cause meadow-wide C losses. A related study mapping blue C in this meadow showed an increase in meadow-wide sediment C stocks from 2013 to 2016, despite the localized loss of sediment C in the inner meadow (Oreska et al, 2020). Our study confirms these findings and shows that disturbance from a MHW can have non-uniform effects on seagrass loss and recovery and on sediment C stock persistence at the meadow-scale (km 2 ).…”
Section: Spatial and Temporal Patterns In Blue C Losssupporting
confidence: 85%
“…Carbon offset credits may provide an avenue to finance seagrass restoration; voluntary credits are now available under a seagrass offset-credit accounting framework administered by Verra (formerly the Verified Carbon Standard Program). Assigning credits under this framework requires knowledge of the net carbon offset that a seagrass restoration project can generate over the project period, typically 30 years (Needelman et al, 2018;Oreska et al, 2020). As we show here, short-term disturbances can interrupt restoration trajectories, potentially altering the net carbon offset through time.…”
Section: Implications For Seagrass Blue C Under Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Site salinity, a proxy for sulfate availability, is the best-established predictor of CH 4 emissions from tidal wetlands, but it weakly constrains emission rates 6,7 . Overall, CH 4 emissions from tidal wetlands are extremely variable, and many sites emit CH 4 at rates that exceed C sequestration in terms of CO 2 equivalents 2,8,9 . Drivers of variability in CH 4 emissions other than sulfate are poorly understood 7,10 .…”
mentioning
confidence: 99%
“…There is strong interest in the role of vegetated coastal ecosystems in climate mitigation, arising from their high rates of carbon accumulation and significant ‘blue carbon’ stocks. However, quantifying those benefits also requires information on the counteracting emissions of greenhouse gases, primarily methane (CH 4 ) (Oreska et al., 2020; Rosentreter, Maher, Erler, Murray, & Eyre, 2018). In this context, we welcome the new global synthesis of methane emissions from mangrove forests, salt marshes and seagrasses by Al‐Haj and Fulweiler (2020), despite their worrying conclusion that the global marine methane production has previously been grossly underestimated with the possible loss of net climatic benefit of mangroves and salt marshes.…”
mentioning
confidence: 99%